\frac { d 2 y } { d x ^ { 2 } } - 4 y = x \sinh x
Solve for d
\left\{\begin{matrix}d=\frac{d_{2}y}{x^{2}\left(x\sinh(x)+4y\right)}\text{, }&y\neq 0\text{ and }d_{2}\neq 0\text{ and }x\neq 0\text{ and }y\neq -\frac{x\sinh(x)}{4}\\d\neq 0\text{, }&y=-\frac{x\sinh(x)}{4}\text{ and }d_{2}=0\text{ and }x\neq 0\end{matrix}\right.
Solve for d_2
d_{2}=\frac{dx^{2}\left(x\sinh(x)+4y\right)}{y}
y\neq 0\text{ and }d\neq 0\text{ and }x\neq 0
Graph
Share
Copied to clipboard
d_{2}y-4ydx^{2}=x\sinh(x)dx^{2}
Variable d cannot be equal to 0 since division by zero is not defined. Multiply both sides of the equation by dx^{2}.
d_{2}y-4ydx^{2}=x^{3}\sinh(x)d
To multiply powers of the same base, add their exponents. Add 1 and 2 to get 3.
d_{2}y-4ydx^{2}-x^{3}\sinh(x)d=0
Subtract x^{3}\sinh(x)d from both sides.
-4ydx^{2}-x^{3}\sinh(x)d=-d_{2}y
Subtract d_{2}y from both sides. Anything subtracted from zero gives its negation.
\left(-4yx^{2}-x^{3}\sinh(x)\right)d=-d_{2}y
Combine all terms containing d.
\left(-x^{3}\sinh(x)-4yx^{2}\right)d=-d_{2}y
The equation is in standard form.
\frac{\left(-x^{3}\sinh(x)-4yx^{2}\right)d}{-x^{3}\sinh(x)-4yx^{2}}=-\frac{d_{2}y}{-x^{3}\sinh(x)-4yx^{2}}
Divide both sides by -4x^{2}y-\sinh(x)x^{3}.
d=-\frac{d_{2}y}{-x^{3}\sinh(x)-4yx^{2}}
Dividing by -4x^{2}y-\sinh(x)x^{3} undoes the multiplication by -4x^{2}y-\sinh(x)x^{3}.
d=\frac{d_{2}y}{x^{2}\left(x\sinh(x)+4y\right)}
Divide -d_{2}y by -4x^{2}y-\sinh(x)x^{3}.
d=\frac{d_{2}y}{x^{2}\left(x\sinh(x)+4y\right)}\text{, }d\neq 0
Variable d cannot be equal to 0.
d_{2}y-4ydx^{2}=x\sinh(x)dx^{2}
Multiply both sides of the equation by dx^{2}.
d_{2}y-4ydx^{2}=x^{3}\sinh(x)d
To multiply powers of the same base, add their exponents. Add 1 and 2 to get 3.
d_{2}y=x^{3}\sinh(x)d+4ydx^{2}
Add 4ydx^{2} to both sides.
yd_{2}=dx^{3}\sinh(x)+4dyx^{2}
The equation is in standard form.
\frac{yd_{2}}{y}=\frac{dx^{2}\left(x\sinh(x)+4y\right)}{y}
Divide both sides by y.
d_{2}=\frac{dx^{2}\left(x\sinh(x)+4y\right)}{y}
Dividing by y undoes the multiplication by y.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}